Highly Active Antiretroviral Therapy (HAART) and Circulating Markers of Immune Activation: Specific Effect of HAART on Neopterin - Amirayan-Chevillard, Nathalie (American Society for Microbiology, 2000)
The circulating levels of immune activation markers, including neopterin, tumor necrosis factor receptor type II, and interleukin-2 receptors, are increased in human immunodeficiency virus-infected patients. We show here that highly active antiretroviral therapy significantly decreased neopterin levels. This effect is reversible, since neopterin levels increased after the arrest of treatment. Their determination may be useful in the evaluation of the efficacy of antiretroviral therapy.